2016
DOI: 10.17222/mit.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Metal particles size influence on graded structure in composite Al2O3-Ni

Abstract: The aim of this study was to investigate the effect of the nickel particle size on the changes in metallic phase content in the graded structure in the Al2O3-Ni composites. Centrifugal slip casting was chosen as the method of composite fabrication. This method allows the creation of a graded distribution of Ni particles in the hollow cylinder composite sample. Functional graded materials were prepared in the vertical rotation axis. In the experiments the following powders were used: a-Al2O3 TM-DAR from Taimei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…A combination of classical slip casting with centrifugal force for alumina/nickel system allows to receive variable distribution of the metallic particles in a composite material. The gradient is obtained due to the different speeds in liquid medium of particles with different density [10]. The technology of the preparation of composites with a zonal distribution of the metallic phase by centrifugal-slip casting can be used for producing composite sleeve-shaped parts with a metallic phase concentration gradient (intended, e.g., for transporting a toxic medium) or parts with increased mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of classical slip casting with centrifugal force for alumina/nickel system allows to receive variable distribution of the metallic particles in a composite material. The gradient is obtained due to the different speeds in liquid medium of particles with different density [10]. The technology of the preparation of composites with a zonal distribution of the metallic phase by centrifugal-slip casting can be used for producing composite sleeve-shaped parts with a metallic phase concentration gradient (intended, e.g., for transporting a toxic medium) or parts with increased mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…The centrifugal slip casting (CSC) combines the effects of slip casting and centrifugation [15,[18][19][20]. The use of porous gypsum molds in the CSC method allows the removal of the liquid medium from the slurry what leads to densification of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous own research has shown that in centrifugal slip casting method lower value of centrifugal acceleration can be applied than in the classical method of centrifugal casting of the composites with the metal matrix [15,19]. This technology allows to obtain the finished product in the shape of a hollow cylinder [15,[18][19][20] characterized by high relative density after sintering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seramik-metal kompozitler yüksek dayanım ve sertlikle birlikte yüksek kırılma tokluğu, aşınma ve termal drenç gibi özelliklerin bir kombinasyonuna sahip olmalıdır. Bu gibi özellikler FDM'ler ile sağlanabilir [2]. Fonksiyonel derecelendirilmiş malzemeler ihtiyaç duyulan tasarıma bağlı olarak farklı yöntemler ile üretilebilirler.…”
Section: Introductionunclassified